Naturally Killing the Silent Killer: NK Cell-Based Immunotherapy for Ovarian Cancer - Nersesian, Sarah; Glazebrook, Haley; Toulany, Jay; Grantham, Stephanie R.; Boudreau, Jeanette E. (Frontiers in Immunology, 2019)
Ovarian cancer (OC) is diagnosed in approximately 22,000 women in the US each year and kills 14,000 of them. Often, patients are not diagnosed until the later stages of disease, when treatment options are limited, highlighting the urgent need for new and improved therapies for precise cancer control. An individual's immune function and interaction with tumor cells can be prognostic of response to cancer treatment. Current emerging therapies for OC include immunotherapies, which use antibodies or drive T cell-mediated cancer recognition and elimination. These have been largely ineffective in OC due to inter- and intra-tumoral heterogeneity, lack of targetable antigens, loss of tumor human leukocyte antigen (HLA) expression, high levels of immunosuppressive factors, insufficient immune cell trafficking and adverse side effects. Natural killer (NK) cells may be ideal as primary or collateral effectors to these nascent immunotherapies. NK cells exhibit multiple functions that combat immune escape and tumor relapse: they kill targets and elicit inflammation through both antigen-specific and antigen-independent pathways and detect loss of HLA as a signal for activation. NK cells are efficient mediators of tumor immune surveillance and control, suppressed by the tumor microenvironment and rescued by immune checkpoint blockade. NK cells are regulated by a variety of activating and inhibitory receptors and are already known to be central effectors across an array of existing therapies. In this article, we highlight interactions between NK cells and OC, their potential to change the immunosuppressive tumor microenvironment, and participate in durable immune control of OC.